An evaluvation of the self-esteem of women sports participant in various games - Muthu, A; Jayanthi, V; Sakthigananavel, D (International Multidisciplinary Research Journal, 2011)
The present study was conducted in Tamil Nadu state, India with the objective of studying self-esteem of women sports participant in different games. Exploratory research design was adopted for the study. The total sample comprised of 90 playing women in which 30 were Kho - Kho / Kabaddi players, 30 were Badminton / Ball Badminton / Volley Ball players and 30 were Squash Rackets / Table Tennis / Fencing / Tennis players. Self esteem scale developed by Verma and Kapadia was used to collect the data. The investigators personally met the respondents by going to their place and administered the tests and collected the data. Among all the three categories of women sports participants, the Squash Rackets / Table Tennis / Fencing / Tennis were having high level of self esteem followed by Badminton / Ball Badminton and Kho - Kho / Kabaddi players. Collectively as one group, most of them were having high and medium level of self esteem reflecting that sports performance of women promotes esteem of women. Through correlation it was found that education and playing experience were significantly and positively related to self esteem of women sports participants. Hence women with higher education and higher playing experience had higher self esteem.